2013
DOI: 10.1182/blood-2012-12-471953
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proposed human B-1 cells reveals pre-plasmablast phenotype

Abstract: B cells have been described as the human counterpart of murine B-1 B cells, but this is controversial.• Our data demonstrate a preplasmablast but not a B-1 phenotype for this population of cells.Controversy has arisen about the nature of circulating human CD20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 33 publications
7
75
2
1
Order By: Relevance
“…2 On the contrary, we feel that the analysis by Li et al 1 supports and extends our findings. Both our analysis and theirs are compatible with the notion that the putative B1 cells have a phenotype intermediate between memory B cells and plasmablasts.…”
Section: Responsesupporting
confidence: 72%
See 2 more Smart Citations
“…2 On the contrary, we feel that the analysis by Li et al 1 supports and extends our findings. Both our analysis and theirs are compatible with the notion that the putative B1 cells have a phenotype intermediate between memory B cells and plasmablasts.…”
Section: Responsesupporting
confidence: 72%
“…2 However, this assertion contradicts the Rothstein group's previous publications in which the inability of human "B1" cells to differentiate to plasmablasts was twice claimed to distinguish B-1 cells from preplasmablasts.…”
Section: 7mentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, Griffin et al (5) claimed the discovery of a small subset of human CD20 ϩ B cells expressing CD27 and CD43 that recap the functional characteristics of murine B-1 cells. However, controversy has arisen about the nature of these cells, and we recently showed that CD27 ϩ CD43 ϩ B cells are in fact activated cells on their way to plasma cell differentiation (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Ce puissant signal de prolifération agit de concert avec l'action de cytokines ou de ligands qui stimulent la sécrétion d'anti- [14,15]. En outre, l'existence des B1 chez l'homme, du moins selon la définition proposée, est de plus en plus controversée puisque la caractérisation de ces cellules B1 présumées révèle en réalité un phé-notype préplasmablastique correspondant à un stade précoce de la différenciation plasmocytaire [16]. Il est cependant intéressant de noter que les cellules B spéci-fiques de la phosphorycholine (PC) se trouvent de façon prédominante, quoique non exclusive, parmi les cellules IgM + IgD + CD27 + [17].…”
Section: Igdunclassified